Identification of High School Students Misconceptions on The Biogeochemical Cycle Topics - Astuti, Yeni Dwi; Meilinda*, Meilinda; Dewi, Safira Permata; Wulandari, Ratu Mutiara; Jajuri, Titiyaka (Jurnal Pendidikan Sains Indonesia, 2024)
Misconceptions are a learning problem that not only impacts student acceptance in the form of delays in receiving new knowledge, but also causes misinformation in society, especially in the publication media.This study aims to identify students' misconceptions by using a three-tier diagnostic test on biogeochemical cycle topics. The first step in identifying misconceptions is to develop an identification instrument using the Treagust development method in several stages, starting from identifying the material, analyzing common misconceptions, and compiling questions at each tier. The results of the development of the instrument show that the three tier diagnostic test instrument has a content validity ratio (CVR) and content validity index (CVI) validity of 1 and a reliability of 0.90 for answer choices and 0.86 for reason choices. The valid and reliable instruments were tested on 210 students in 6 accredited schools A, B, and C in South Sumatra, Indonesia. The results showed that on biogeochemical cycle topics, there were two sub-topics categorized as experiencing high misconceptions, fifteen in the moderate category, and eight in the low category. Misconceptions occur in the sub-topics in a cycles of water, carbon and oxygen, sulfur, and nitrogen. The results of the analysis also showed that the highest misconception of 64% was in the reduction and oxidation sub-topic of the sulfur cycle. These findings can be used as input for educators in South Sumatra and Indonesia in general in teaching biogeochemical cycle material to avoid similar misconceptions in the future